Oil palm production in the 20th century and beyond: the impact of climate change in Malaysia - Wan Mohd Noor, Wan Noranida; Mohd Nawi, Nolila; Buda, Mark; Kai Seng, Kelly Wong (Department of Agribusiness, Universitas Muhammadiyah Yogyakarta, 2024)
The widespread concern about the devastating impact of climate change, especially in the agricultural sector, has become severe. This paper aims to explore and predict the impact of climate change on oil palm production using future climate conditions projected by the National Water Research Institute of Malaysia (NAHRIM). An error correction model (ECM) and autoregressive distributed lags (ARDL) cointegration approach were applied to assess the short-run and long-run impact of climate change on oil palm production. The estimated short-run coefficients disclosed that the oil palm own price and fertilizer use positively affected oil palm production in the second lag period, and increased acreage benefited oil palm production in the long run. The rainfall variable negatively affected the second lag period but positively rose oil palm production in the long run. The results of forecasting analysis revealed that SN1 (minimum climate variability), SN2 (maximum climate variability), and SN3 (average climate variability) would increase oil palm production by 5%, 1%, and 2%, respectively. Meanwhile, the oil palm yield would rise from 16.73 t/ha in 2020 to 16.89 t/ha in 2030 under SN1. However, with maximum rainfall, the yield would drop to 16.41 t/ha in 2030. Overall, climate change would likely reduce oil palm yield. This research could serve as empirical guides for policymakers and oil palm stakeholders in terms of practical and policy implications to adapt to climate change-related risks and uncertainties. The practical cover investments in technologies, such as developing drought-tolerant and early-maturity crop varieties, boosting water saving, and reducing evapotranspiration.